Does the End Justify the Means? the Farc and Drug Trafficking as a Related Crime [¿El Fin Justifica Los Medios? Las Farc y el Narcotráfico Como Delito Conexo] - Jiménez-Cabrera, D (Escuela Militar de Cadetes, 2020)
The use of drug trafficking as the main funding source of The Revolutionary Armed Forces of Colombia (FARC) led to its consideration in the Havana peace talks. If its rebellion was financed by drug smuggling, this would compel the Special Jurisdiction for Peace to consider it as a related crime to political crime in the Final Agreement’s framework, prompting the question, is it legally possible to consider drug-trafficking a related crime? This article is structured into five sections. The first, historically describes the context in which the armed conflict evolved. The second discusses the theoretical relationship between drug trafficking, international conflict, and international law. The third analyzes the concepts of political crime and related crime according to doctrinal debate. From a legal stance, the fourth validates if drug trafficking constitutes a related crime. From these, conclusions are drawn. © Encounters in Theory and History of Education.